The study of job performance among employees in Royal Malaysian Customs Johor Bahru / Nur Azrin Muhammad Idrus and Mohd Azreen Arbain - Muhammad Idrus, Nur Azrin; Arbain, Mohd Azreen (2014)
This research was conducted to study the effectiveness of job performance among employees of Royal Malaysia Customs in Johor Bahru. A review of employee perceived training effectiveness relationship to employee attitudes literature by Tsai et al. (2007), found that employees committed to learning showed a higher level of job satisfaction with a positive effect on their performance. Harrison et al. (2006) point out that job attitudes and job performance are two of the most enduring concepts in organizational research. Besides that, job performance of employees plays a crucial factor in determining an organizational performance. Highly performing individuals will be able to assist organization to achieve its strategic aims thus sustaining the organization competitive advantage (Lado & Wilson, 1994: Dessler, 2011). Thus, labour force will have to be well equipped with the right skills and prepare to ensure businesses do not lose out due to lack of ability to compete both nationally and internationally (Tomaka, 2001). Job satisfaction (Robbins, 2005) defined job satisfaction as a collection of feelingsthat an individual hold towards his or her job. Numerous factors influence employee job satisfaction, as reviewed by Rad & Yarmohammadian (2006). Job satisfaction has been observed to affect levels of job dissatisfaction, absenteeism, grievance